2003
DOI: 10.1034/j.1600-079x.2003.00072.x
|View full text |Cite
|
Sign up to set email alerts
|

Human circadian melatonin rhythm phase delay during a fixed sleep–wake schedule interspersed with nights of sleep deprivation

Abstract: The human circadian pacemaker, with an intrinsic period between 23.9 and 24.5 hr, can be reset by low levels of light. Biomathematical models of the human clock predict that light-dark cycles consisting of only approximately 3.5 lux during 16 hr of wakefulness and 0 lux during 8 hr of sleep should entrain approximately 45% of the population. However, under real-life conditions, sleep-wake schedules and the associated light-dark exposures are often irregular. It remains unclear whether the phase of the pacemake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 48 publications
5
25
1
Order By: Relevance
“…Further in agreement with the current data, a phase delay in the melatonin rhythm has previously been reported after one night of sleep deprivation (Cajochen et al, 2003), and an increase in melatonin levels was found in young subjects during extended wakefulness (up to 50 h) (Zeitzer et al, 2007). The latter study, however, also described an age-dependent difference in melatonin profiles, with young subjects exhibiting reduced and older subjects exhibiting elevated melatonin levels during one night of sleep deprivation compared to habitual sleep.…”
Section: Discussionsupporting
confidence: 80%
“…Further in agreement with the current data, a phase delay in the melatonin rhythm has previously been reported after one night of sleep deprivation (Cajochen et al, 2003), and an increase in melatonin levels was found in young subjects during extended wakefulness (up to 50 h) (Zeitzer et al, 2007). The latter study, however, also described an age-dependent difference in melatonin profiles, with young subjects exhibiting reduced and older subjects exhibiting elevated melatonin levels during one night of sleep deprivation compared to habitual sleep.…”
Section: Discussionsupporting
confidence: 80%
“…The finding of previous studies (Voultsios et al, 1997;Cajochen et al, 2003) indicates posture does not appear to affect the MO. Blood was drawn through an intravenous saline-lock, usually placed in the forearm.…”
Section: Measurement Of Endogenous Pineal Melatonin Productionmentioning
confidence: 66%
“…The role of light exposure is determined by a number of parameters, such as light intensity, and duration and pattern of exposure (Sack et al 2007). Our measurements showed light intensities that ranged between 3 and 243 lux at night in the ship's compartments and it has been suggested that even dim light of 5-13 lux may slightly suppress melatonin (Cajochen et al 2003). Light intensity did not vary in the ship's working areas, and the duration of exposure lasted for the whole shift, i.e., 12 h, interrupted only by meal breaks and operation halts.…”
Section: Discussionmentioning
confidence: 91%